Mangunan pine forest-based discovery e-module: Effective in improving students’ learning independence and scientific literacy? - Putri Prima Renanthera; S. Suhartini (Universitas Muhammadiyah Malang, 2026)
Backround- Biology learning should train students independence learning to optimize their science literacy. Objectives-Develop a discovery learning e-module based on the Mangunan pine forest to enhance the independence learning and science literacy of Phase E students on the topic of ecosystems. Methods-This research utilized the ADDIE design model for development. The study was conducted from January 2024-February 2025 at State Islamic High School 4 Bantul, Yogyakarta, Indonesia. The research subjects were media and teaching material experts, subject matter experts, biology teachers, and students. Feasibility and practicality data were collected through product assessment sheets, independent learning through self-assessment sheets, and scientific literacy using essay questions. Feasibility and practicality data were analyzed both descriptively and quantitatively, while effectiveness was assessed using N-Gain and one-way MANOVA. Results-E-module was feasible and practical as a teaching material. The effectiveness test results showed that the N-Gain values for learning independence and science literacy in the experimental group were greater than those in the control group. The one-way manova test results showed that the e-module had a simultaneous effect on learning independence and science literacy. Conclusions-Involving the Mangunan pine forest in the discovery e-module can be an innovation in biology education, training students' learning independence and literacy.